THE EFFECT OF ACCOUNTABILITY, TRANSPARENCY AND SUPERVISION ON THE PERFORMANCE OF THE VALUE FOR MONEY BUDGET - Ratih, Dewi; Ratnawati, Dyah (International Journal of Economy, Education and Entrepreneurship (IJE3), 2023)
It is important to study the implementation of accountability, transparency and oversight in the performance of budgets with a value for money concept in government organizations. The purpose of this study is to examine the effect of accountability, transparency, and oversight on budget performance with a value for money concept. This study used a quantitative approach with the subject of analysis being employees of the finance sector at the Public Works and Public Housing Agency, Kab. Mojokerto, which has 67 employees. The data analysis technique uses SPSS 26. This study shows that transparency has a significant effect on the performance of the budget with a value for money concept, while accountability and oversight have no significant effect on the performance of the budget with a value for money concept